Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. Smart leadership as an entry point to achieving competitive advantage in the Al-Kharj Governorate Education Department Mrs. Munirah Abdullah Al-Masoud , Dr. Zainab Awwad Mofleh Darwish 2. The Obstacles of Implementing Blended Learning Teaching from the Perspectives of Intellectual Disabilities Teachers in Jeddah Mrs. Seham Hamadi Al-Sulami, Dr. Lama Abdul Hakeem Sahab 3. The Impact of the Variation of Digital Story’s Presentation Patterns (static graphics animations) in Problem-Solving Based Learning on Developing Computer Skills for Middle-School Female Students Mrs. Imtinan Mohammed Alzughaibi ,Prof. Mohammed Ibrahim Alshuwaie 4. Attitudes of Human Resources in the Department of Education in Al-Kharj Governorate Towards Blended Training Mrs. Noura Sultan Al-Dossary, Prof. Ajlan Mohammad Al-Shehri 5. Reasons for the low achievement in mathematics among students of the first three grades of the basic education stage from the viewpoint of teachers and educational supervisors in Benghazi city - Libya Lecturer Fatma Naser Ali Mohamed, Dr. Bothaina Fadil Bukhatwa , Mrs. Haajer Ayad Mohamed Alagelee 6. Cognitive Bias and Its Relationship to the Level of Information Processing among Umm Al-Qura University Female Students Mrs. Ehklas Ahmed Alharbi, Prof. Newar Mohammed Saad Alharbi 7. Rationing the Test of Mathematic Ability (TOMA3.) on high classes primary school students (boys) at Gunfudah Educational Directorate Mr. Khader Mohammed Al-Zailay